Measurement of serum C reactive protein concentration after bone marrow transplantation for leukaemia. Issue 3 (March 1984) - Rowe, I F; Worsley, A M; Donnelly, P; Catovsky, D; Goldman, J M; Galton, D; Pepys, M B
Abstract : C reactive protein concentration was measured serially in 19 patients with leukaemia after bone marrow transplantation. Six episodes of graft versus host disease occurred in the presence of fever but with no evidence of infection, and these were associated with C reactive protein concentrations as high as 200 mg/l. C reactive protein values were also increased in 12 febrile episodes associated with infection, in seven of which graft versus host disease was also present. C reactive protein concentrations are of no value in differentiating infection from graft versus host disease, but in both cases they may be useful as an objective index of response to appropriate treatment.